Invisible Bruises: Theoretical and Practical Considerations for Black/Afro-Latina Survivors of Childhood Sexual Abuse. Issue 3 (2nd October 2019) - Sanchez, Delida; Benbow, Luz Márquez; Hernández-Martínez, Martha; Serrata, Josephine V.
Abstract: This article focuses on the intersectionality of race, gender, and violence in the lives of Black/Afro-Latinas who have experienced childhood sexual abuse. First, we discuss the trauma of slavery, racism, and colonization in Latin America and the Caribbean, which objectifies Black bodies and renders Blackness invisible. Second, we identify institutional and interpersonal barriers to seeking trauma support. Third, we present preliminary findings from a Listening Circle among survivors who participated in the Black Latinidad: Building Siblinghood to End Child Sexual Abuse Project. Finally, we propose a racially and culturally specific, trauma-informed approach that draws on the strengths of survivors and centralizes their voices and how to intervene.